EFFECT OF TRANSFORMATIONAL LEADERSHIP, COMPENSATION AND EMPLOYEE DEVELOPMENT ON WORK MOTIVATION MSME EMPLOYEES IN MEDAN CITY - Surianto Zalukhu, Rika; Piter Sony Hutauruk, Rapat; Collyn, Daniel (RADJA PUBLIKA, 2022)
This study aims to examine the effect of transformational leadership, compensation and employee development on the work motivation of MSME employees in Medan City. The dependent variable of the study is work motivation, while the independent variables of the study include transformational leadership, compensation and employee development. This research is quantitative descriptive. The study was conducted on employees of 15 Food and Beverage SMEs in Medan City, amounting to 120 people. The sampling method used is the saturated sample. The type of data used is primary data. The data collection method used a questionnaire distributed online to 120 respondents. From a total of 120 questionnaires distributed, as many as 100 questionnaires returned with complete data for the measurement of all variables. Methods of data analysis using multiple linear regression analysis method. The results showed that transformational leadership partially had a positive and significant effect on the work motivation of MSME employees in Medan City. Likewise, compensation and employee development are partially concluded to have a positive and significant effect on the work motivation of MSME employees in Medan City.